BIOTECHNOLOGY OF RECOMBINANT HORMONES IN DOPING - Biljana Vitošević; Zdravko Vitošević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Recombinant DNA technology has allowed rapid progress in creating biosynthetic gene products for the treatment of many diseases. In this way it can produce large amounts of hormone, which is intended for the treatment of many pathological conditions. Recombinant hormones that are commonly used are insulin, growth hormone and erythropoietin. Precisely because of the availability of these recombinant hormones, it started their abuse by athletes. Experiments in animal models confirmed the potential effects of some of these hormones in increasing physical abilities, which attracted the attention of athletes who push the limits of their competitive capability by such manipulation. The risks of the use of recombinant hormones in doping include serious consequences for the health of athletes. Methods of detection of endogenous hormones from recombined based on the use of a monoclonal antibodies, capillary zone electrophoresis and protein biomarkers